Result of slaughter, cutting and fatty acid composition of beef of charolais bulls and steers - Holló, Gabriella; Zándoki, Rita; Pohn, Gabriella; Vargáné Visi, Éva; Repa, Imre (Acta Agraria Kaposváriensis, 2005)
During the last decades the consumer requirements for beef have been basically changed. The consumers prefer the meat of young animals, which are poor in fat and choose the adequately marbling meat because of its tenderness and eating quality. Within the frame of this study our aim was to analyse the slaughter value and beef quality of charolais bulls (n = 6) vs. steers (n = 5). The slaughter weight of animals was 651.63 + 60.32 kg. The dressing percentage was 60.86 + 3.86%, between the genders there were significant differences. From the results it can be concluded, that the fat content of the right half carcass was in case of steers significantly higher. The crude fat content of longissimus in steers can be seen more prosperous considering eating quality. The effect of gender on SAFA and the n-3 fatty acid content were significant. The PUFA content of steers is more beneficial from human nutritional point of view.
Keywords: fatty acid composition; charolais; bull; steer